DAMPAned Methotrexate: A Case Report and Review of the Management of Acute Methotrexate Toxicity. Issue 1 (December 2019) - Young, Ann; Beriault, Daniel; Jung, Benjamin; Nikonova, Anna; Abosh, Dory; Lee, Samantha; Zaltzman, Jeff; Perl, Jeffrey
Rationale: Consensus guidelines on the management of methotrexate-induced nephrotoxicity using glucarpidase (Voraxaze) may be relatively unfamiliar to the nephrology community. Presenting concerns of the patient: A 61-year-old man with intravascular large B-cell lymphoma was admitted for cycle #1 of high-dose methotrexate (HDMTX) following 2 cycles of R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) chemotherapy. On admission, he was clinically euvolemic and had a creatinine clearance of 98 mL/min. He received standard HDMTX toxicity prophylaxis with volume expansion, urinary alkalinization, and leucovorin rescue. Diagnoses: Despite prophylactic efforts, he developed a severe acute kidney injury, creatinine 63 to 226 µmol/L (2.56 mg/dL), following HDMTX, impaired methotrexate clearance, and neurotoxicity manifested by status epilepticus. Interventions: He was given glucarpidase to convert extracellular methotrexate into its inactive metabolites, glutamate and DAMPA (4-deoxy-4-amino- N 10 -methylpteroic acid) at 52 hours post-HDMTX. Cross-reactivity between commercial methotrexate immunoassays with DAMPA led to falsely elevated methotrexate concentrations for much longer than expected based on the current guideline (5 days instead of <48 hours). This required ongoing monitoring of methotrexate concentration by mass spectrometry. Outcomes: The patient remained nonoliguric and did not develop acute indications for dialysis. Serum creatinine peaked at 608 µmol/L (6.88 mg/dL) 6 days after HDMTX. He ultimately had a full renal and neurologic recovery. Lessons learned: Glucarpidase is an effective option for nonrenal elimination of methotrexate-induced nephrotoxicity. Timing of methotrexate concentration monitoring to assess for toxicity, how to access the drug, and the need for ongoing monitoring by mass spectrometry beyond the guideline recommendation are highlighted for centers where HDMTX therapy may be used.